THE CORRELATION BETWEEN HYPERTENSION AND COGNITIVE FUNCTION - Elvina Zuhir (International Journal of Healthcare Research, 2018)
Background: Rapid increase in Indonesia health development lead to increase in life expectancy. This demographical shift implicated in altering disease pattern to dominate be degenerative diseases, such as hypertension. Hypertension affected morbidity and mortality rate significantly. Hypertension also known to correlated with increasing risk in cerebrovascular diseases that continue to cognitive function disorders such as vascular dementia.Â Objective: To know the relationship between hypertension and cognitive function.Methods: Using cross-sectional design with comparative study. Blood pressure measured by using sphygmomanometer and stethoscope, while cognitive function measured by using Mini Mental State Examination (MMSE) and Raven Progressive Matrices (RPM). This research was held in M. Djamil Hospital, Puskesmas Nanggalo Siteba, Puskesmas Padang Pasir, Puskesmas Alai, Puskesmas Andalas, Puskesmas Seberang Padang dan Puskesmas Pauh with consecutive sampling techniqueResult: There is no significant differentiation based on age and gender in hypertension and normotensive sample. There is significant differentiation in cognitive function in hypertension and norm tension sample (p-value< 0,05). Hypertension sample will have 7,8 times risk to had cognitive function disorders than normotensive sample (measured using MMSE; OR: 7,8). Hypertension sample will have 3,3Â  times risk to had cognitive function disorders than normotensive sample (measured using RPM; OR: 3,3).Conclusion: There is significant differentiation in cognitive function in hypertension and normotensive sample. Hypertension subject will have 3,3 to 7,8 times risk to had cognitive function disorders than normotensive